ETNOZOOLOGI SUKU DAYAK KANAYANT DI DESA TEMAHAR KECAMATAN JELIMPO KABAUPATEN LANDAK - Almey GP, Benediktus; Anwari, M Sofwan; Yani, Ahmad (JURNAL HUTAN LESTARI, 2020)
The utilization of protected animals is feared to accelerate the rate of animal extinction if there is no field observation related to the use of animals by the Kanayant Dayak tribe in Temahar village. Related data and animal species, animal parts and circumchations are preliminary indicators to determine the benefits and functions of the animal itself. The method used in this research is the survey method of selecting respondents using the Snowball sampling method, data collection using questionnaire assistance. The results showed the use of animals as much as 16 types. For the ritual of Adat 3 types, treatment 8 types and mystical 5 types. The main parts are meat, bile, fur, heart, blood, kidney, pedals, scales, eggs, liver, and head. Kanayant Dayak people cultivate animal meat for traditional ritual, treatment and mystical by means of cooking gravy and burnt, most people still use traditional equipment to cook and burn meat and for hunting.Keywords: Ethnozoology, Kanayant Dayak, Medicine, Mysticism, Traditional Rituals.